Bianchi Type-IX Cosmological Model in Self-Creation Theory of Gravitation. Issue 1 (2nd January 2021) - Nimkar, A.S.; Wath, J.S.; Wankhade, V.M.
Abstract: In this paper, we study macroscopic body cosmological model in the context of self-creation theory. We solve field equations by using relation between metric coefficients and equation of state for macroscopic body. Also, we discuss the features of the obtained solutions.